Information Transductions in the Bioavailability of Image Representations - Silva, Stephanie Cerqueira [UNESP]; Sant’Ana, Ricardo César Gonçalves [UNESP]; Jorente, Maria José Vicentini [UNESP] (Universidad de Antioquia, 2025)
Digital images are inherently more fragile and malleable; thus, they are more susceptible to transformations during their info-communication processes. In digital-virtual environments, such processes traverse a range of layers that directly result in the encapsulation of information in viewing interfaces. In this context, the central issue of this article is to understand how the information transductions of digital images occur for their bioavailability in the viewing layer. The main objective is to verify the possible information transformations that occur in the form, content, and metadata of digital images displayed on the Open Art Images interface compared to those on Wikimedia Commons, through the observation of transduction processes in data feedback. Methodologically, the study is qualitative, employing a descriptive-exploratory research approach. Based on collections and image file verification, a comparative analysis was conducted to identify transductions during the transfer from one environment to another. The analyses showed information transformations during their flow, corroborating a likely unawareness of netizens concerning the information in images. The study concluded that informational encapsulation helps mask the transduction processes present in their layers, thereby favoring the netizens’ informational asymmetry.
Transducciones informativas en la biodisponibilidad de las representaciones de imágenes
Transduções informacionais na biodisponibilidade de representações imagéticas
Keywords: digital-virtual environments; image representation; information; Information transduction; technology